2005
DOI: 10.1074/jbc.m500322200
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Nuclear Factor of Activated T Cells Activation Signaling Suppresses Balloon Injury-induced Neointima Formation in a Rat Carotid Artery Model

Abstract: We have previously reported that nuclear factor of activated T cells (NFATs) play an important role in the regulation of vascular smooth muscle cell migration and proliferation by receptor tyrosine kinase and G proteincoupled receptor agonists, platelet-derived growth factor-BB and thrombin, respectively. To understand the role of NFATs in vascular disease, we have now studied the involvement of these transcription factors in neointima formation in a rat carotid artery balloon injury model. The levels of NFATc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 47 publications
5
88
0
Order By: Relevance
“…We have reported previously that NFATs mediate injuryinduced vascular wall remodeling (16,19,20). In this study, we show that SM-specific NFATc1 knockdown, although having no effect on Rac1 stimulation, attenuates MCP1-induced cyclin D1 expression, CDK6 and CDK4 activities, and Pak1 activation.…”
Section: Discussionsupporting
confidence: 50%
“…We have reported previously that NFATs mediate injuryinduced vascular wall remodeling (16,19,20). In this study, we show that SM-specific NFATc1 knockdown, although having no effect on Rac1 stimulation, attenuates MCP1-induced cyclin D1 expression, CDK6 and CDK4 activities, and Pak1 activation.…”
Section: Discussionsupporting
confidence: 50%
“…41,42 In VSMCs, the expression of NFATc1 is much higher than that of NFATc3 whereas NFATc2 and NFATc4 are not detectable. 43 Subcellular localization of NFATc1 in SMC (U8A4 cell line) varies under different differentiation state: 1) widely stained in the cytoplasm in dedifferentiated SMC; 2) perinuclear in differentiated SMC; and 3) nuclear in very differentiated cells.…”
Section: Nfatc1 and Nfatc4mentioning
confidence: 99%
“…Adenoviral Vectors-Construction of Ad-GFP and Ad-GFPVIVIT was described previously (19). The human cyclin D1 was amplified by PCR using the following primers 5Šˆ-TTA ACC GTC GAC ATG GAC TAC AAA GAC CAT GAC-3Šˆ (forward) and 5Šˆ-ACA GGG ATG CCA CCC GGG ATC CTC TAG-3Šˆ (reverse) from the p3XFLAG-cyclin D1 expression vector (26) and subcloned into SalI and BamHI sites of pBlueScript.…”
Section: Transient Transfections and Luciferasementioning
confidence: 99%
“…Towards understanding the mechanisms of NFATs in the regulation of VSMC migration, we have shown that these transcriptional factors mediate interleukin-6 expression as one of the effector molecules in receptor tyrosine kinase (RTK) and G protein-coupled receptor (GPCR) agonist-induced VSMC motility (18). In addition, we have reported the involvement of NFATs in injury-induced neointima formation (19). Recently, we have also demonstrated that activation of NFATc1 causes up-regulation of the cell cycle dependent gene, cyclin A2, leading to increased CDK2 activity in VSMCs and the progression of these cells through the cell cycle (20).…”
mentioning
confidence: 99%